2018
DOI: 10.1016/j.archger.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of body composition, pain and resilience on physical activity, physical function and physical performance at 2 months post hip fracture

Abstract: The purpose of this study was to test a model of the factors influencing physical activity, physical function and physical performance at 2 months post hip fracture and compare model fit between men and women. Age, cognitive status, comorbidities, pain, resilience, bone mineral density, total body lean mass, total body fat and grip strength were hypothesized to be directly and/or indirectly related to physical activity, physical function and physical performance. This analysis used data from the seventh Baltim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…It is commonly agreed, however, that resilience contributes to well-being and quality of life when confronting adversities and hence may be a key resource for aging well. Some previous studies have shown that higher levels of resilience are associated with higher levels of physical activity (Perna et al 2012 ; Resnick et al 2018 ) and social participation (Levasseur et al 2017 ). However, it is unclear whether resilience contributes to active aging among people facing mobility impairments.…”
Section: Introductionmentioning
confidence: 98%
“…It is commonly agreed, however, that resilience contributes to well-being and quality of life when confronting adversities and hence may be a key resource for aging well. Some previous studies have shown that higher levels of resilience are associated with higher levels of physical activity (Perna et al 2012 ; Resnick et al 2018 ) and social participation (Levasseur et al 2017 ). However, it is unclear whether resilience contributes to active aging among people facing mobility impairments.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, individuals may have different responses to pain such as resilience and/or beliefs about pain that may affect how they respond to pain stimulus irrespective of race. 26,27 Individuals may experience similar chronic pain but their physical responses to the pain may differ based on how they perceive their pain or even how long they have lived with the pain.…”
Section: Discussionmentioning
confidence: 99%
“…associations between fat mass and pain [50,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], nine studies examined adiposity within a specific muscle [68][69][70][71][72][73][74][75], five studies did not specify a site of pain [76][77][78][79], two studies only examined multisite pain [80,81], and three studies examined pain in children [82][83][84].…”
Section: Plos Onementioning
confidence: 99%